2016
DOI: 10.1002/cssc.201501691
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into CO2 Absorption Mechanisms with Amino‐Acid Ionic Liquids

Abstract: The last decade saw an explosion of interest in using amine-functionalized materials for CO2 capture and conversion, and it is of great importance to elucidate the relationship between the molecular structure of amine-functionalized materials and their CO2 capacity. In this work, based on a new quantitative analysis method for the CO2 absorption mechanism of amino-acid ionic liquids (ILs) and quantum chemical calculations, we show that the small difference in the local structure of amine groups in ILs could le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 51 publications
4
59
0
Order By: Relevance
“…The further shifts to δ =182.0, 159.2, and 30.4 ppm observed after absorption of another 1.25 mol of CO 2 was attributed to the cooperative N–CO 2 –O interactions . A signal at δ =158–162 ppm in the 13 C NMR spectra of ILs containing basic anions is usually observed in the presence of CO 2 and is generally assigned to the carbonate‐ or carbamate‐type carbonyl groups, formed by the “strong” interaction of the N‐ and/or O‐containing anions with CO 2 (Scheme S1) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The further shifts to δ =182.0, 159.2, and 30.4 ppm observed after absorption of another 1.25 mol of CO 2 was attributed to the cooperative N–CO 2 –O interactions . A signal at δ =158–162 ppm in the 13 C NMR spectra of ILs containing basic anions is usually observed in the presence of CO 2 and is generally assigned to the carbonate‐ or carbamate‐type carbonyl groups, formed by the “strong” interaction of the N‐ and/or O‐containing anions with CO 2 (Scheme S1) …”
Section: Methodsmentioning
confidence: 99%
“…Zanatta containing basic anions is usually observed in the presence of CO 2 and is generally assigned to the carbonate-or carbamatetype carbonyl groups,f ormed by the "strong" interaction of the N-and/or O-containing anions with CO 2 (Scheme S1). [5][6][7][8][9][10][11][12][13][14][15][16][17] At this point, we would like to note that ashift of around 159 ppm is also the chemical shift ( 13 C{ 1 H} NMR spectra) of ILs associated with bicarbonate anions [12,18,19] or ILs containing dissolved bicarbonate. [20] Moreover,i th as already been demonstrated that the formation of bicarbonate, [21] resulting from the reaction of CO 2 with the confined water in imidazolium ILs associated with basic imidazolate and acetate anions, [22] or wet amino acid containing ILs, [12] is responsible for ar esonance observed around d = 159 ppm in the 13 Cs pectrum.…”
mentioning
confidence: 99%
“…However, glutamate‐ and aspartate‐based ionic liquids generally have higher glass transition temperatures, melting temperatures, and viscosities. These ionic liquids have potential applications in catalysis, chiral separations, gas separation and purification, CO 2 absorption, oil purification, coal and biomass pretreatment, as biolubricants, and as solvents for organic syntheses, such as Cu‐free Sonogashira coupling reactions or peptide synthesis …”
Section: Amino Acids In the Synthesis Of Ionic Liquidsmentioning
confidence: 99%
“…Although a high absorption capacity of CO 2 has been realized in ILs, the fundamental rules that govern the absorption mechanism and performances are still not clear, which may hamper a rational design and development of ILs in this respect. In addition, currently the rationales for the catalytic performance of PILs on CO 2 absorption were almost entirely based on the acidity data determined in molecular solvents, such as water or DMSO (Wang et al, 2010; Yang et al, 2016). It is known from both experimental results and theoretical calculations that the acidity obtained in molecular solvents may not explain acid/base behavior in ILs satisfactorily (Mihichuk et al, 2011).…”
Section: Introductionmentioning
confidence: 99%